Treatment - (:unkn) unknown (Springer Nature, 2021)
Glucocorticoids (GC) are required for remission-induction in patients with Takayasu’s arteritis. Remission is usually achieved with high-dose (1 mg/kg/dayor pulse) regimens. A non-biologic disease modifying agent such as methotrexate, azathioprine or leflunomide is suggested as a first-line approach. In relapsing or refractory patients biologic agents tumor necrosis factor inhibitors or tocilizumab are chosen as second-line treatments. Except in acute ischemic episodes, vascular interventions should be performed in remission phases and under immunosuppressive regimens. © 2021, Springer Nature Switzerland AG.
Keywords: Biologic agents; Glucocorticoids; Tocilizumab; Tumor necrosis factor inhibitors